2000
DOI: 10.1017/s0272263100003065
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Information Organization to Second Language Acquisition Studies

Abstract: The present cross-linguistic study deals with the relevance of principles of information organization in adult second language acquisition. It looks at typological features of information structure that allow speakers to organize and shape the flow of information when carrying out complex tasks, such as giving a description, and pinpoints factors that lead to the selection of linguistic form. At the focus of our attention are means used in reference introduction, such as existential and locational construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 17 publications
4
60
1
9
Order By: Relevance
“…These relations between the more-and less-prominent take the form of topic, focus, presupposition and assertion relations between the constituents of an utterance. The acquisition of information structure by adult L2 learners has previously been examined as it relates to the syntactic constructions employed by L2 learners in discourse and narrative (e.g., Carroll et al 2000). Some previous studies have used production data to examine the acquisition of finiteness in L2 learners of French (Schlyter 2003) and German (Dimroth et al 2003;Dimroth 2008); others have studied anaphora in narrative (Carroll and Lambert 2003), the production of topic markers (Ferdinand 2002), and the grammatical means used to organize information in learner varieties of German and English (Carroll & von Stutterheim 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These relations between the more-and less-prominent take the form of topic, focus, presupposition and assertion relations between the constituents of an utterance. The acquisition of information structure by adult L2 learners has previously been examined as it relates to the syntactic constructions employed by L2 learners in discourse and narrative (e.g., Carroll et al 2000). Some previous studies have used production data to examine the acquisition of finiteness in L2 learners of French (Schlyter 2003) and German (Dimroth et al 2003;Dimroth 2008); others have studied anaphora in narrative (Carroll and Lambert 2003), the production of topic markers (Ferdinand 2002), and the grammatical means used to organize information in learner varieties of German and English (Carroll & von Stutterheim 2003).…”
Section: Introductionmentioning
confidence: 99%
“…les volumes collectifs de Dimroth & Lambert 2008, Han & Cadierno 2010, Pavlenko 2011. Le décalage entre productions natives et non natives se situe aussi bien au niveau de la macro-que de la micro-planification (Levelt 1989) et peut concerner, par exemple, l'unité sémantique choisie pour construire des chaînes anaphoriques dans des discours articulés (Carroll & von Stutterheim 1997, Caroll et al 2000, Lambert, Carroll & von Stutterheim 2008, l'ancrage déictique vs. holistique des événement relatés dans les récits, la segmentation du flux événementiel en unités discrètes (Noyau et al 2005), l'attention portée au déroulement vs. point final de la situation (Stutterheim, Nüse & Serra 2002, Stutterheim 2003, l'entité éligible au rôle de sujet grammatical (Carroll & Lambert 2003, Ahrenholz 2005, ainsi que la distribution de l'information nouvelle (rhème) vs. ancienne (thème) dans l'énoncé (Bohnacker & Rosén 2008).…”
Section: L'acquisition De La Perspective Discursive En L2unclassified
“…For the sake of clarity, contexts containing a switch on the polarity will be referred to as "polarity-switch contexts", whereas linguistic expressions that highlight a contrast on the polarity component as "polarity contrast markers". Effects of typological differences on the L2-encoding of information structure in high-proficient non-native speakers have already been investigated in a number of linguistic domains, such as temporality, space and referential movement (e.g., Carroll & Lambert, 2006;Carroll, Murcia-Serra, Watorek, & Bendiscioli, 2000;Hendricks & Hickmann, 2011;von Stutterheim & Lambert, 2005) including the pragmatic category of polarity contrast (Benazzo, Andorno, Interlandi, & Patin, 2012). In particular, by using the film-retelling elicitation procedure as in Dimroth et al (2010), Benazzo et al (2012) found that German non-native speakers of Italian or French tend to recruit lexicogrammatical marking that highlight the polarity component, which is more in line with their L1 perspective.…”
Section: Introductionmentioning
confidence: 99%